Enhancing Manufacturing-as-a-Service Supply Chain Transparency With Master-Slave Multi-Chain and SQS-PBFT - Pengliang Qiao (IEEE Access)
Addressing challenges such as centralization, data tampering, and information silos within traditional supply chain transparency frameworks, we leverage the decentralized, immutable, and traceable attributes of blockchain technology. Given the multitude of participating nodes and the extensive volume of tracking data in Manufacturing-as-a-Service (MaaS) supply chains, we initially propose a master-slave multi-chain data storage model tailored for MaaS supply chain transparency. Building upon this, to enhance blockchain performance in this context and address the issues of high communication overhead, low consensus efficiency, and the absence of dynamic mechanisms inherent in the Practical Byzantine Fault Tolerance (PBFT) method, we introduce the Service Quality Scoring Based Practical Byzantine Fault Tolerance (SQS-PBFT) method. By incorporating the service quality scoring model for optimal master node selection, we aim to improve consensus efficiency; through the node tiering mechanism and consensus protocol optimization, we reduce communication costs; and by establishing the dynamic node mechanism for flexible node entry and exit, we enhance system flexibility. Experiments demonstrate that with an increasing number of nodes, the proposed SQS-PBFT method results in about 29.47% lower communication overhead, about 25.11% higher throughput, about 19.98% reduced latency, and about 36.15% reduced malicious behavior, thus offering improved consensus efficiency and serving as a reference for MaaS supply chain transparency.